Selir Wandhan dalam Panji Jayalengkara Angreni: Tinjauan Sastra Bandingan Teks Panji dan Babad - Yudhistira, Naufal Anggito; Limbong, Priscila Fitriasih; Suhardjo, Rias Antho Rahmi (Perpustakaan Nasional RI, 2023)
Panji’s literary works in Java became a form of sign or pasemon in Javanese culture. Many of the narratives in Panji’s texts relate to Javanese traditional historiography. This research will focus on the story about Putri Wandhan in the Panji Jayalengkara Angreni text and the Babad texts. This study uses a comparative literary method and considers that Putri Wandhan’s narrative in the Panji Jayalengkara Angreni text contains a collective memory of history in the past. The emergence of the narrative about Putri Wandhan in Panji Jayalengkara Angreni and other Javanese literature is due to the contact of the Javanese and East Indonesian people in the past. In this study it was found that the story of Putri Wandhan describes the efforts of Javanese poets in the past to show the superiority of the Javanese kingdoms. In addition, this story is also a pasemon of the political life of the kingdoms in Java in the past. The story of the concubine from Wandhan in Panji Jayalengkara Angreni is an attempt to describe the superiority of the Javanese kings and an effort to honor their ancestors.